2019
DOI: 10.1002/jum.15151
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Artery Corrected Flow Time and Respiratory Variations of Peak Blood Flow Velocity for Prediction of Hypotension After Induction of General Anesthesia in Adult Patients Undergoing Elective Surgery: A Prospective Observational Study

Abstract: Objectives Hypotension is common after induction of general anesthesia, and intraoperative hypotension is associated with postoperative end‐organ injury such as acute kidney injury and myocardial ischemia. This study was designed to determine the utility of the carotid corrected flow time (cFT) and carotid artery peak blood flow velocity variation (ðVpeak) for prediction of hypotension after induction of general anesthesia. Methods Adult patients (n = 112) undergoing any elective surgery under general anesthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 32 publications
1
31
0
Order By: Relevance
“…We have found that CAPVV is also a poor predictor of PSH. Our result agrees with the results of Maitra et al ,[ 22 ] who reported CAPVV to be a poor predictor of post-induction hypotension in patients receiving general anaesthesia for elective surgeries. CAPVV >18.8% could predict hypotension with only 61.9% sensitivity and 67.4% specificity in their study.…”
Section: Discussionsupporting
confidence: 93%
“…We have found that CAPVV is also a poor predictor of PSH. Our result agrees with the results of Maitra et al ,[ 22 ] who reported CAPVV to be a poor predictor of post-induction hypotension in patients receiving general anaesthesia for elective surgeries. CAPVV >18.8% could predict hypotension with only 61.9% sensitivity and 67.4% specificity in their study.…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, recent investigations have observed that common carotid artery FTc predicts postinduction hypotension. 20,21 Our study has limitations. First, we did not study actual hemorrhage; however, the LBNP model does correlate well with blood loss in nonhuman primate studies 14 and diminished thoracic blood volume.…”
Section: Discussionmentioning
confidence: 92%
“…Ostensibly, a patient deemed to have mild-to-moderate SV reduction by common carotid Doppler assessment would be at increased risk of hypotension following initiation of mechanical ventilation. Indeed, recent investigations have observed that common carotid artery FTc predicts postinduction hypotension 20,21 …”
Section: Discussionmentioning
confidence: 99%
“…42 FTc also detects clinically significant gastrointestinal hemorrhage 43 and hypotension after induction. 44 Further, FTc anticipates SV changes during blood donation and in response to a PLR following blood donation. 45,46 Similar findings are noted in healthy individuals who fast.…”
mentioning
confidence: 99%
“…When the cardiovascular stress is cyclical intrathoracic pressure change induced by passive, mechanical ventilation, common carotid artery peak systolic velocity variation is also an accurate functional hemodynamic measure. 39,44,[50][51][52][53] Importantly, however, when respiration is controlled (even partially) by the patient, peak velocity variation-such as pulse-pressure and stroke-volume variation-usually underperforms as a functional measure. Nevertheless, one group found that carotid artery peak velocity variation worked well in spontaneously breathing preoperative neurosurgery patients, 51 and another group could not replicate this finding in critically ill patients.…”
mentioning
confidence: 99%